Low-level laser therapy (LLLT) as a possible resource to attenuate muscle damage in delayed onset muscle soreness (DOMS) - Rodrigues, N. C. (2014)
The aim of this study was to investigate if the infrared laser irradiation can prevent or minimize delayed onset muscle soreness (DOMS). Eight healthy male were divided in two groups: laser group and sham laser group. All volunteers were submitted to an Eccentric Exercise Protocol (EEP) for biceps brachii to induce muscle damage. Active laser (780 nm; 50 mW; 500 mW/cm2; 12 J/cm2; energy of 5 J per point applied for 20 s on four points) or sham were applied two times, before and after EEP. Maximal voluntary contraction, range of motion, muscle soreness, creatine kinase activity, lactate, C-reactive problem, IL-6, IL-8, Ferric Reducing Capacity of Plasma and total bilirubin were analyzed before, 8, 24, 48, 72, 120 and 168 h after EEP. LLLT decreased IL-6 levels after 8 h of eccentric exercise in laser group. No significant differences were observed in other systemic markers of inflammation, antioxidant status or in muscle performance between groups. The results suggest a partial attenuation of muscle damage, as laser therapy was able to reduce IL-6 levels.